Stress reactions cannot explain the gender gap in willingness to compete - Thomas Buser; Anna Dreber; Johanna Möllerström (Research Institute of Industrial Economics (IFN), 2015)
Women are often less willing than men to compete, even in tasks where there is no gender gap in performance. Also, many people experience competitive contexts as stressful and previous research has documented that men and women sometimes react differently to acute stressors. We use two laboratory experiments to investigate whether factors related to stress can help explain the gender gap in competitiveness. Experiment 1 studies whether stress responses (measured with salivary cortisol and through self-assessment) to taking part in a mandatory competition predict individual willingness to participate in a voluntary competition. We find that while the mandatory competition does increase stress levels, there is no gender difference in this reaction. Cortisol response does not predict willingness to compete for men but is positively and significantly correlated with choosing to enter the voluntary competition for women. In Experiment 2 we exogenously induce stress using the cold-pressor task. We find no causal effect of stress on competitiveness for the sample as a whole and only tentative evidence of a positive effect for women. In summary, even though there are some gender differences in the relation between stress responses and the decision to enter a competition or not, these cannot explain the general gender gap in willingness to compete that is generally found in the literature and which we replicate.
Keywords: C90; C91; J16; J71; 330; Gender differences; competitiveness; experiment; cortisol; stress